Lazer mercadoria e juventude: relações entre o público e o privado a partir do caso concreto da Boate Kiss - Nascimento, Thaiane Bonaldo do (2016)
This research aimed to "analyze the relationship between leisure in nightclubs in the city of Santa Maria, Brazil in the legislation field" from a concrete reality: the disaster of the Nightclub KISS. As a methodological approach, we retreated from the "police investigation of Nightclub KISS" documental analysis; matters from print media "Diário de Santa Maria" from 2013 and 2014, and the Complementary Law No. 14.376, from the 26th of December 2013. And, as a mean of interpretation, we used the assumptions from the content analysis. We listed the categories for analysis: leisure as a merchandise, university students, nightclubs, legislation, Nightclub KISS, risk and safety. The analysis of the documents showed: the articulation of the leisure as a merchandise, youth and risks to the logic of capitalist production system; and that the youth search for ecstasy in leisure, and the owners search for profit relegates to second plan the aspects related to safety, in particular, infrastructure and the licenses. Moreover, the precariousness of public leisure in the city of Santa Maria makes private leisure facilities, with greater emphasis on nightclubs and the main leisure areas of the university students, which constitute themselves as merchandise, and trade desire in an alienated way. In this context, the disaster was not an accident but the result of several flaws. In short, the infrastructure and the management of safety regulations require observation and questioning beyond the condescension and the uncritical acceptance of social trends and leisure fetishization. The creation of legislations that would guarantee security to nightclubs after the disaster, especially the Law Kiss, constituted a landmark in the country. Nevertheless, the subsequent of Law Kiss, explained that the economic system and private interests remain being the great limiter of politics and hence the relationship between the public and private sectors. In the capitalist system, security is not a first-order component, it‟s the opposite, vanishes at the expense of the primary concern: profit.